Subinhibitory concentrations of antibiotics affect development and parameters of Helicobacter pylori biofilm - Krzyżek, Paweł; Migdał, Paweł; Tusiewicz, Kaja; Zawadzki, Marcin; Szpot, Paweł (Frontiers in Pharmacology, 2024)
Helicobacter pylori causes chronic gastric diseases in nearly 50% of people around the world. It is suggested that biofilm formation has a pronounced effect on the dynamic resistance spread and recurrence of these infections. To mimic the scenario of therapeutic ineffectiveness, we investigated the impact of sub-minimal inhibitory concentrations (sub-MICs) of antibiotics on the development and parameters of biofilms produced by clinical H. pylori strains. We observed that constant exposure to metronidazole or levofloxacin stimulated the speed of autoaggregation and the amount of extracellular matrix, resulting in increased dimensions of the developed biofilms. Contrary to this, continuous exposure to clarithromycin negatively affected a number of stress-related reactions and led to the biofilm-weakening effect. Through assessing the membrane fatty acid profiles of antibiotic-exposed cells, we confirmed that metronidazole and levofloxacin induced a biofilm-like phenotype, while clarithromycin kept bacteria in a planktonic form. Our results suggest that sub-MICs of antibiotics affect the biochemical and biophysical properties of the developing biofilm of H. pylori strains and may impact the effectiveness of antibiotic treatment.